Transforming Primary School Science Education: The Quantum Teaching Revolution - Siahaan, Jadi Hatoguan; Marson, Ferrant; Forsyth, Oyelana (Jurnal Ilmu Pendidikan dan Humaniora, 2022)
In a world characterized by rapid technological advancements and evolving educational needs, the quest for innovative teaching methodologies has never been more crucial. This research delves into the transformative potential of quantum teaching in the realm of primary school science education. Quantum teaching, inspired by the principles of quantum physics, reimagines the classroom as a dynamic arena for holistic learning, critical thinking, active engagement, and creativity. The study investigates the holistic nature of quantum teaching, emphasizing the interconnectedness of scientific concepts, and the promotion of critical thinking skills essential for scientific inquiry. It explores the practical implications of implementing quantum teaching, including curriculum design, teacher training, classroom dynamics, and assessment methods. The research reveals how quantum teaching can enhance student engagement, foster problem-solving abilities, and ignite a passion for science. It underscores the significance of this research in the context of educational improvement and the field of primary school science, as it paves the way for more dynamic and effective educational practices. This research contributes to the existing body of knowledge by introducing innovative teaching methods, emphasizing holistic learning, critical thinking, active engagement, and flexibility. It underscores the importance of creativity, interdisciplinary connections, student-centered learning, and data-driven educational improvement. By preparing students for the future, this research advances the dialogue on educational enhancement and the evolving landscape of education in a dynamic world. In conclusion, this research signifies the beginning of a new era in primary school science education, urging educators, parents, communities, and policymakers to embrace the quantum teaching frontier and unlock the potential of a new generation of scientists and thinkers.